Work and non-work identities in global virtual teams: Role of cultural intelligence in employee engagement. Issue 1 (28th January 2020) - Shaik, Farheen Fathima; Makhecha, Upam Pushpak; Gouda, Sirish Kumar
Abstract : Purpose: Increasing digitization has transformed ways of work in modern age. Organizations are increasingly relying on global virtual teams (GVTs) as new forms of working. However, the challenges of configuration of GVTs have been reported to reduce the levels of employee engagement, especially so in multicultural GVTs. Extant research indicates cultural intelligence as one of the drivers of employee engagement in GVTs, though the nature of this relationship has remained unclear. As there is scarce literature on the nature of this relationship, the purpose of this paper is to examine the linkages between cultural intelligence and employee engagement and the authors explain the findings using the identity lens. Design/methodology/approach: This study is an ethnographic inquiry to understand the nature of the relationship between cultural intelligence and employee engagement. Findings: The results of the study indicate that the inclusionary pressures of non-work identities (national culture) are high in context of GVTs owing to their configuration. However, preferences (alignment or misalignment) of team members either initiate gain cycles or loss cycles, thus effecting the levels of employee engagement. Further, it was found that individual preferences may dynamically change from misalignment toward alignment with improved levels of cultural intelligence among team members of GVTs. The relationship between cultural intelligence and employee engagement has been found to be mediated by trust among team members in GVTs. Originality/value: This is one of the first papers to understand the dynamics of this relationship in an organizational GVT context. The authors also propose a unique framework combining cultural intelligence, trust and employee engagement in the context of GVTs.